A probabilistic forecast of the immigrant population of Norway - Nico Keilman (Statistics Norway, Research Department, 2023)
We present a probabilistic forecast for the immigrant population of Norway and their Norwegian-born children ("second generation") broken down by age, sex, and three types of country background: 1. West European countries plus the United States, Canada, Australia, and New Zealand; 2. East European countries that are members of the European Union; 3. other countries. First, we compute a probabilistic forecast of the population of Norway by age and sex, but irrespective of migration background. The future development of the population is simulated 3 000 times by stochastically varying parameters for mortality, fertility and international migration to 2060. We add migrant group detail using stochastically varying random shares to split up each result from the previous step into six sub-groups with immigration background, and one for the non-immigrants. The probabilistic forecast is calibrated against the Medium Variant of Statistics Norway's official population projection.
Keywords: C15; J11; 330; stochastic forecast; immigrants; second generation; random share method